The Role of Digital Technologies in Activating Archaeological Tourism – Babil Governorate (Czech Journal of Multidisciplinary Innovations, 2025)
One of the recent trends currently prevailing in the travel and tourism sector in the 21st century is digital tourism. This paper set out to discuss the notion of digital tourism, the nature of digital tourism technologies, processes of the digital tourism experience as well as the archaeological tourist sites of greatest importance in Babil. The research was descriptive-analytical in nature and a random sample of tourists made of 156 people was used to gather the data through the questionnaire. The results made it clear that the digital technologies can play a very important role in stimulating archaeological tourism in Babil Governorate. The research also presented a number of recommendations such as considering digitalization in the strategy of tourism development in Iraq and utilizing the experiences of other countries in digital tourism to apply it in archaeological sites in Babil.